A Review of the Research Status and Development Trends of Dexterous Hand Technology - Yan , Mengjie; Guo, Yuhan (International Journal of Mechanical and Electrical Engineering, 2025)
Dexterous hands are pivotal for enabling advanced robotic manipulation. This review synthesizes recent advances in structural design, actuation, sensing, and control algorithms. Structurally, trends shift from serial/parallel mechanisms toward hybrid rigid-soft biomimetic designs. Actuation leverages electromagnetic, fluidic, and smart-material systems for improved precision and compliance. Multi-modal sensing—integrating force, position, tactile, and vision data—enhances environmental awareness. Control algorithms evolve from classical PID to intelligent strategies like neural networks and reinforcement learning for adaptive manipulation. Persistent challenges include flexibility-stability trade-offs, sensing latency, and high costs. Future directions emphasize AI integration, lightweight designs, and improved reliability for complex tasks in industrial and biomedical applications.